Analysis of Algebraic Operational Problem-Solving Ability in Terms of Adversity Quotient - Ditya Paramitha; Lisa Dwi Afri (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
The adversity quotient (AQ) is used in this study to describe a person's ability to solve algebraic operations problems. Grade VIII students of Intelligent Pure MTs are the focus of this research. Data collection techniques included tests of problem-solving abilities, adversity quotient (AQ) questionnaires and interviews as part of a descriptive qualitative research method. Miles and Huberman's model and data reduction were used to analyze the data. The results showed that students who had high remaining bad luck (AQ) (Climber) were able to dominate markers of critical thinking skills, and their experimental results reached a score of 90; students who had moderate remaining difficulties (AQ) (Camper ) did not entirely dominate the problem capacity indicators and experimental results. They achieve a score of 70, students with low residual Luck (AQ) (Quitter) cannot master the problem ability indicators, and the test results reach a score of 50. And the conclusion from the results of the problem-solving test on algebraic operations is that the higher the students' Adversity quotient (AQ), The higher (Climber), the better the results obtained in completing solving problems in algebraic operations. Keywords: problem-solving, algebraic operations, adversity quotient.